The supply chain imperative - Neef, Dale, 1959- (American Management Association, 2004)
The new business imperative is to create an unambiguous culture of ethical behavior. The Supply Chain Imperative presents a framework any business can use for monitoring, reporting, and improving performance of suppliers on environmental, social, and other issues. The book ensures that the company's ethical mandate is understood and implemented along the entire length of the chain, helping companies avoid costly litigation and potentially devastating injury to reputation brought on by violations of law and ethical norms.